2018
DOI: 10.1515/chem-2018-0118
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Application of Zinc and Vanadium Complexes against Diabetes Mellitus a Coronary Disease: A review

Abstract: During the last two decades, number of peoples suffering from diabetes has increased from 30-230 million globally. Today, seven out of the ten top countries are suffering from diabetes, are emergent countries. Due to alarming situations of diabetes, chemists and pharmacist are continuously searching and synthesizing new potent therapeutics to treat this disease. Now a days, considerable attention is being paid to the chemistry of the metal-drug interactions. Metals and their organic based complexes are being u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…Cu(II) complexes have been used as representatives of these essential-endogenous metals because copper is one of the most important trace elements involved in several enzymatic and protein functions in metabolism ( Ruiz-Azuara and E Bravo-Gomez, 2010 ; Correia et al, 2015 ; Boodram et al, 2016 ; Nunes et al, 2020 ). Promising activities of copper-based coordination compounds for target-specific next-generation anticancer therapeutics have previously been reported ( Azam et al, 2018 ). Cu(II) complexes of 2-phenyl-3-hydroxy-4(1 H )-quinolinone (O,O donor) and other nitrogen-containing (N,N donor) ligands, such as 2,2′-bibyrdine and 1,10-phenanthroline derivatives, showed promising cytotoxicity against human breast cancer cell lines (MCF-7) ( Buchtik et al, 2012 ; Johnstone et al, 2016 ), while 1,10-phenanthroline and 2,2′-bipyridine based Cu(II) complexes showed superior in vitro and in-vivo antitumor activity when compared to cisplatin ( Ruiz-Azuara and E Bravo-Gomez, 2010 ; Correia et al, 2015 ; Nunes et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cu(II) complexes have been used as representatives of these essential-endogenous metals because copper is one of the most important trace elements involved in several enzymatic and protein functions in metabolism ( Ruiz-Azuara and E Bravo-Gomez, 2010 ; Correia et al, 2015 ; Boodram et al, 2016 ; Nunes et al, 2020 ). Promising activities of copper-based coordination compounds for target-specific next-generation anticancer therapeutics have previously been reported ( Azam et al, 2018 ). Cu(II) complexes of 2-phenyl-3-hydroxy-4(1 H )-quinolinone (O,O donor) and other nitrogen-containing (N,N donor) ligands, such as 2,2′-bibyrdine and 1,10-phenanthroline derivatives, showed promising cytotoxicity against human breast cancer cell lines (MCF-7) ( Buchtik et al, 2012 ; Johnstone et al, 2016 ), while 1,10-phenanthroline and 2,2′-bipyridine based Cu(II) complexes showed superior in vitro and in-vivo antitumor activity when compared to cisplatin ( Ruiz-Azuara and E Bravo-Gomez, 2010 ; Correia et al, 2015 ; Nunes et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…52 Several reports have also shown that other metal ion−flavonoid complexes such as copper and iron complexes may also show biological activity through their ability to interact with DNA or through alterations of the membrane fluidity. In a seminal study, the antidiabetic effects of several zinc and vanadyl complexes with nonflavonoid organic ligands were made, which revealed the insulin-mimetic effect of both sets of complexes with the zinc complexes exhibiting a slightly better effect on reducing free fatty acid release from adipocytes as well as lowering blood glucose while the vanadyl complexes inhibited protein tyrosine phosphatase 1B, a key target implicated in type 2 diabetes 53 However, comparison of the biological activities of vanadium−flavonoid and other metal ion-flavonoid complexes has still not been made to decide upon the benefits of the use of vanadium complexes. Figure 3 depicts the diverse range of molecular targets reported for the biological activities of the flavonoid− vanadium complexes.…”
Section: Vanadium-based Complexesmentioning
confidence: 99%
“…For example, vanadyl salts have been employed as antidiabetes for more than a century and vanadium (IV) and vanadium (V) complexes have explored for their insulin-mimetic properties [1]. Significant number of publications has appeared on the biological role different oxidation states of vanadium in medicine [2]. VO 2+ is referred to as the most stable existing diatomic ion which forms diverse stable cationic, anionic and neutral complexes when coordinated to a large variety of ligands particularly with most electronegative donor groups [3].…”
Section: Introductionmentioning
confidence: 99%
“…Major studies on vanadium have focused on the development of vanadium(IV) or -(V) complexes with organic ligands as delivery agents that improve gastrointestinal absorption and reduce the toxicity of vanadate [4], [5]. The role of metal complexes in relation to biological activity has been recently pursued [2], [6]. The features of some drugs enable them to play vital role as bio-ligands in the biological systems.…”
Section: Introductionmentioning
confidence: 99%